Sofosbuvir and Ribavirin in Turkish non-cirrhotic chronic hepatitis C patients infected with genotype 2 or 3 - Bal, Tayibe; Cabalak, Mehmet (Annals of Medical Research, 2021)
Aim: Few studies have evaluated real-world clinical experience with sofosbuvir (SOF) plus ribavirin (RBV) in hepatitis C virus (HCV) genotypes 2 and 3 infections from Turkey. Thus, this study aimed to investigate the results of sofosbuvir plus ribavirin therapy in genotype 2 and 3 cases followed in an infectious disease clinic at a university hospital in Hatay, southern Turkey. Material and Methods: In this single-centre, retrospective, observational study, 58 eligible patients treated with SOF/RBV (400 mg of SOF plus weight-based RBV) therapy between October 2016 and February 2019 were examined. Forty-three patients who had completed the duration of treatment and had known virological response status were evaluated for treatment outcomes. Results: SOF/RBV achieves a sustained virological response (SVR) rate of 96.3% and 100% in the HCV genotype 2 and 3 groups, respectively, with treatment duration of 12-24 weeks. No patient experienced a virologic breakthrough while only one experienced virologic relapse after the completion of therapy. The incidence of adverse events was 25.5% (11/43) while the most common (11.6%) adverse event was ribavirin-related hemolytic anemia. Conclusion: The current study revealed that the SOF/RBV therapy achieved excellent response rates with a good safety profile in non-cirrhotic Turkish patients infected with HCV genotype 2 or 3.